Private joys and public joys: Per celebrare la contingenza - Baptist, Gabriella (B@belonline, 2022)
Personal emotions and feelings are opportunities for openness and hope that can represent a new vital energy which leads us to rethink coexistence in the balance between social needs and personal autonomy, public good and private happiness. Crucial is the question of an affectivity capable of opposing any destructive narcissism, investing one’s libido in the precariousness of the world and in contingency. In this context, democratic experience is understood by Marcella D’Abbiero as a celebration of the finite, which has to leave room for the dimension of desire. Jean-Luc Nancy had also argued for a similar perspective in a pamphlet defending the legacy of the French Sixty-Eight.